Induction of Secretagogue Independent Gastric Acid Secretion via a Novel Aspirin-Activated Pathway - Kitay, Alice Miriam; Ferstl, Florentina Sophie; Link, Alexander; Geibel, John Peter (Frontiers in Physiology, 2019)
Aspirin has been widely recommended for acute and chronic conditions for over 2000 years. Use of either single or repetitive doses are commonly used for analgesic and antipyretic reasons and to prevent heart attacks, stroke and blood clot formation. Recent studies show that it can also be used chronically to dramatically reduce the risk of a variety of cancers. However prolonged usage of aspirin can cause severe damage to the mucosal barrier, increasing the risk of ulcer formation and GI-bleeding events. In the present study, we show the effects of acute low dose aspirin exposure as an active secretagogue inducing gastric acid secretion. Studies were performed with isolated gastric glands using the pH sensitive dye BCECF-AM to assess acid secretion. The non-selective NOS inhibitor L-NAME (30µM), or the specific inhibitor ODQ (1H-1,2,4Oxadiazolo4,3-aquinoxalin-1-one). were applied while monitoring intracellular pH The effects of basolateral exposure to aspirin (acetylsalicylic acid, ASA) caused activation of gastric acid secretion via the H+, K+-ATPase. Our data suggest that aspirin increases nitric oxide (NO) production which in turn activates acid secretion. Exposure of gastric glands to either the non-selective NOS inhibitor L-NAME, and the highly selective, soluble guanylyl cyclase inhibitor ODQ (1H-1,2,4Oxadiazolo4,3-aquinoxalin-1-one) effectively inhibited aspirin dependent gastric acid secretion. Aspirin can be considered as a novel secretagogue, in the way that it activates the H+, K+-ATPase. With increased daily aspirin consumption, our findings have important implications for all individuals consuming aspirin even in low doses and the potential risks for increased acid secretion.